Automation of the computer handling of gel reading data produced by the shotgun method of DNA sequencing. - Staden, R (1982)
This paper describes a computer method for handling gel reading data produced by the shotgun method of DNA sequencing. The method greatly reduces the time the sequencer needs to spend checking and editing his data and yet it produces a consensus sequence for which the accuracy of determination of every base can be clearly shown. The program can take a batch of new gel readings, screen them against vector sequences removing any that match, and then compare and align all the sequences to produce a final consensus. No information is lost in this process as alignments are achieved by making only insertions and because all the individual gel readings are added to a database from which they can be retrieved and displayed lined up one above the other. This allows the user to check on the alignments achieved by the program and if necessary change them. As each gel reading is added to the database the consensus is automatically updated accordingly and used for the next comparisons. This is a much faster process than comparing each new gel against every individual gel in the database.